DEEP LEARNING PEDAGOGY GROUNDED IN DAVID AUSUBEL’S LEARNING THEORY: A LITERATURE STUDY - Ali Imron (Al-Mubin, 2025)
The development of education in the global era requires learning approaches that emphasize not only rote memorization but also conceptual understanding, critical thinking skills, and problem-solving abilities. The concept of deep learning in education emerged as a response to this need. David Ausubel’s meaningful learning theory is highly relevant in addressing these challenges, as it emphasizes the importance of linking new knowledge with the learner’s existing cognitive structure. This article aims to analyze the relationship between deep learning and Ausubel’s theory through a literature review of various national and international studies. The findings show that deep learning can be optimized through the implementation of advance organizers, activation of prior knowledge, and progressive differentiation. Therefore, Ausubel’s theory provides a philosophical and methodological foundation for developing meaningful learning practices in schools and universities.